Exploring the potential for a scalable “ECD Change Lab” to invigorate inclusive innovation within the ECD NGO sector and so advance service delivery in underserved communities - Le Mottee, Sherrilee (Graduate School of Business (GSB), 2023)
The gaps in the provision of early childhood care and education in South Africa are persistent. Too many young children are still outside learning programmes, and many women struggle to find ways of ensuring that their young children are cared for while they are at work. In 2015, universal access to ECD services was prioritised at policy level, yet 1.1 million children between three and five years old still do not benefit from early learning programmes. Essentially, this is a failure of our public policy to protect our youngest children, women and the interests of the whole of society. While government has been vocal about its commitments to leading the ECD sector, which has until recently been dominated by non-profit organisations, it has shown itself to be ineffective in bringing about much needed changes in provision. It is well recognised that partnerships between government and civil society organisations can help widen service delivery to reach children and increase the quality of provision they experience. But South Africa's civil society sector has struggled to fill these gaps. In some respects, the sector seems stuck in a quagmire, mirroring government struggles. Given the high level of interest in ECD in South Africa at the moment, there is a window of opportunity for action. This study brings to the fore critical voices to shed light on these challenges through a series of dialogue interviews with thirty key informants from the ECD civil society sector. What emerges is a picture of committed but struggling organisations that have yet to find their way in a changing sector. Donors and investors have altered their way of working as government is now the leader of the sector, and opportunities for engagement are funneled through statemanaged forums. With an eye on sustainability, organisations are doing their best to keep going, while struggling to answer the question “what's next?”. Even though the Integrated ECD Policy (2015) defines a role for civil society organisations, there is still uncertainty and a failure to realise the potential of this group of expert and experienced stakeholders. Actions towards change are fragmented while tensions run high – there seems to be no real plan for what comes next for civil society organisations that is driven by this ‘body'. This study puts forward that an ECD Change Lab process offers a potential route to explore these challenging dynamics and to find new solutions. Change Labs are living laboratories that draw life from processes of collective enquiry, problem framing and solution seeking. The ability of Change Labs to unfreeze and open new channels for innovation and problem- solving are well documented. In this context, it is argued that such a Lab could bring stakeholders together to build trust, plan and create prototypes that can be tested in the field with a view to increased sector resilience and sustainability.